Epilepsy in Neurological Phenotypes of Epidermal Nevus Syndrome - Flores-Sarnat, Laura (Journal of Pediatric Epilepsy, 2016)
Epidermal nevus syndrome (ENS) encompasses a group of congenital genetic disorders characterized by the association of an epidermal nevus with systemic anomalies including the brain. The most frequent subtype with neurological features is linear sebaceous nevus syndrome (LSNS), followed by keratinocytic nevus syndrome (ENS). Both are caused by postzygotic RAS mutations. All forms of ENS are mosaic disorders that share a common embryological basis and pathogenesis as neurocristopathies. The lines of Blaschko indicate the cutaneous migratory pathways of neural crest. Neural crest defects explain the development of nevi and associated multisystemic anomalies: brain, ocular, osseous, muscular, orodental, cardiovascular, endocrine, renal/urinary, and adipose tissue. Epilepsy and cognitive and motor deficits are caused mainly by hemimegalencephaly (HME), a closely related mosaic anomaly caused by somatic mutations in PI3K–AKT3–mTOR pathway that determines overgrowth. The usual onset of epilepsy is in the neonatal period or early infancy, often as infantile spasms. The pioneer description of nevus sebaceous in 1895 by Jadassohn is the basis for delineating the LSNS. The eponym “Schimmelpenning syndrome” as a substitute for that long-established term makes no sense in the context of the large number of authors who contributed to defining this syndrome. A review of 111 cases of LSNS and other subtypes enabled a classification of neurological phenotypes; epilepsy occurred in 77% and HME in 38%. Three distinctive additional syndromes also are within the spectrum of ENS: CLOVES, SCALP, and Heide's syndrome. The impact of epilepsy in patients affected by ENS is related to time of onset and extent of brain anomalies. Timing of the mutation determines the phenotype and severity of the systemic lesions.
Keywords: hemimegalencephaly; neurocristopathy; keratinocytic nevus syndrome; linear sebaceous nevus syndrome; CLOVES syndrome; Heide's syndrome; congenital hemifacial hyperplasia with lipomatosis; timing